PERMAINAN DRUM BAND DARI BAHAN BEKAS UNTUK MENINGKATKAN KECERDASAN MUSIKAL ANAK PADA USIA TK - Herawati, Herawati (Lembaga Penelitian UM Metro, 2016)
This classroom action research was conducted to determine the extent of the benefits drum band toward musical intelligence of children at preschool age. The issues addressed in this study are the benefits of drumming band of scrap materials to enhance the musical intelligence of children at preschool age. This study uses classroom action research (PTK) with 3 cycles and each cycle there are four stages: planning, implementation, observation and reflection. Object of research conducted in kindergarten PKK I Banjarsari Metro Academic Year 2014/2015. The data collection used in this research is the direct observation by the steps of data collection, data analysis and conclusions to determine the extent of the benefits of drumming band of scrap materials to enhance the musical intelligence of children and analyzed descriptively.Based on the research results can be concluded that the method of drumming band of scrap materials can enhance the musical intelligence of children at preschool age. The impacts are children more confident, more enthusiastic and happy in following the teaching and learning process.